Bootspurs of the Early Modern Period Newfoundland - Mathias, Catherine (Material Culture Review, 2015)
For researchers of art history or archaeology of the early modern period, evidence must be viewed through a multidisciplinary eye in order to understand all aspects of culture. Objects which become popular as a costume component can serve as markers for change in culture. This paper will demonstrate the value of one such marker, the bootspur of the 17th century. Examples are taken from an archaeological site in Ferryland, Newfoundland, and from the British Museum. Note that when using this type of research material, there is an additional limitation, that of burial environment. We may never get the whole story because, depending on the material of manufacture, some objects will survive burial and others will not.